Laura Skew Group Algebras - Assem, Ibrahim (2007)
We prove that if A is an artin algebra, G is a finite group acting on A such that |G| is invertible in A, and R=A[G]b is a basic algebra associated with the skew group algebra, then A is left supported (or right supported, or laura, or left glued, or right glued, or weakly shod, or shod) if and only if so is R.